2017
DOI: 10.17576/jkukm-2017-29(2)-02
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Halloysite Nanotubes-Polyvinyl Alcohol Nanocomposites Using Malonic Acid Crosslinked

Abstract: Halloysite nanotubes (HNTs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…This can be attributed to the use of a higher amount (20 phr) of SEBS- g -MA having a lower viscosity than the SEBS matrix polymer, resulting in a reduced solution/dispersion viscosity and relatively faster removal of THF during nanocomposite production, leading to nanotube aggregate formation. 26 It may also be probably due to less amount of THF molecules interacting with the Org-HNT to make it suspended in the solution in the presence of a high amount of SEBS- g -MA molecule.…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the use of a higher amount (20 phr) of SEBS- g -MA having a lower viscosity than the SEBS matrix polymer, resulting in a reduced solution/dispersion viscosity and relatively faster removal of THF during nanocomposite production, leading to nanotube aggregate formation. 26 It may also be probably due to less amount of THF molecules interacting with the Org-HNT to make it suspended in the solution in the presence of a high amount of SEBS- g -MA molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Gaaz et al proved that PVA could become a structurally different polymer with proper mechanical properties and thermal stability due to the thermal stability of HNTs although it had low strength and thermal stability for some applications, [13]. Crosslinking is considered as a well-known technique which is generally applied to enhance the mechanical/thermal properties and increase the solubility of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that the crosslinking process of PVA could be performed by applying dicarboxylic acids like malonic acid (MA) with sulphuric acid as a catalyst to obtain esterification [16,17]. The use of MA crosslinked HNTs-PVA composites significantly improved the thermal/mechanical properties [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in nanoscience and nanotechnology [ 2 ] have facilitated the sciences to develop new polymers hybridized with high refractive index (RI) nanoparticles (NPs). Typically, silicone-hydrogel [ 3 ], poly(vinyl alcohol) [ 4 ] (PVA) CLs [ 5 ], and other plastic polymers [ 6 ], in addition to manufacturing techniques, are used to produce transparent (T > 90%), lightweight, and impact-resistant CLs [ 7 ]. RGP CLs are expensive and suffer from a lack of hydrophilic monomers, but they are more flexible than PMMA CLs due to their integration with low modulus components and high efficiency in reducing generated aberrations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%